La gestión del supermercado virtual: Tipificación del comportamiento del cliente online - Eduard Cristóbal Fransi; Frederic Marimon Viadiu (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
This article analyzes various elements that influence customer buying behaviour of online supermarket. These elements are related to both website aesthetic aspects, as with the processes taking place at the time of purchase. From this analysis, we study the different groups of consumers with homogeneous behaviour and position themselves according to their attitudes. The analysis also defines the e-supermarket service quality provided, and their main dimensions. In the conclusions we mention areas in which the online supermarket manager must accomplish to improve the quality of their service.
Keywords: L81; M31; 330; virtual supermarket; segmentation; e-Commerce; marketing; positioning